Subjects of Memory? On Performing Holocaust Memory in Two German Historical Museums. Issue 3 (1st September 2016) - Dekel, Irit
Abstract : This paper looks at how historical museums in Germany that are not Holocaust or Jewish museums represent Jews. It examines the permanent and temporary exhibitions, as well as their visitors' experiences, at the two largest national and state-sponsored historical museums: the House of History in Bonn and the German Historical Museum in Berlin. I first analyze the ways in which Jewish symbols and images of Jews tell the story of the Holocaust's aftermath in those museums. The article then focuses on a temporary exhibition, 'Shalom: Three Photographers See Germany, ' at the Bonn House of History (August 2015–June 2016). I suggest that the exhibitions create directed viewing, whereby the visitors look at Jews and project the experience of viewing Holocaust images. I argue that as they are presented and viewed in the 'Shalom' exhibition, Jews undergo temporal displacement whereby their subject position and possible roles both in remembering and in being remembered are limited. I conclude by showing that Jews, as well as other Holocaust victim groups and migrant groups in Germany today, are not equal subjects of memory, meaning both that their subjectivity as participants in the public sphere is limited to specific roles, times and spaces, and that inter-subjective communication about their representation is limited.